Productivity and fibre attributes of absorbent Asiatic cotton (Gossypium arboreum) cultivars in rainfed central India - BLAISE, DESOUZA; KRANTHI, KESHAV; SAXENA, SUJATA; VENUGOPALAN, MANGAT V; MOHAN, PUNIT (The Indian Journal of Agricultural Sciences, 2022)
Asiatic cotton (Gossypium arboreum L.) cultivars, possessing short staple length, superior water holding capacity and high micronaire values are considered fit for manufacturing absorbent cotton. Such cultivars are cultivated in north and northeast India. Field studies were conducted at the experimental farm of the ICAR-Central Institute for Cotton Research, Nagpur, from 2013â€“14 to 2015â€“16, to evaluate productivity and fibre properties of Asiatic cotton cultivars from north (race bengalense) and northeast (race cernuum) India vis-Ã -vis the cultivars of central and south India (race indicum). In 2013, RG8 produced the highest seed cotton yield (1759 kg/ha), but did not differ from Phule Dhanwantary (1599 kg/ha) and BG-II hybrid H6 (1518 kg/ha). Averaged over 2014â€“15 and 2015â€“16, AKA8, CNA418, CNA375, CNA423, Phule Dhanwantary and MDLABB (1489 to 1989 kg/ha) gave significantly higher seed cotton yield than BGII hybrid Mallika (953 kg/ha). In general, cultivars from north and northeast India produced less seed cotton yield than those from central and south India. Out of the 13 cultivars, Assam Comilla and Phule Dhanwantary met the Indian Pharmacopoeia standards (fibre length 20 mm, micronaire >6.5, absorbency and sinking time <10 sec and ash content <0.5%). Cultivation costs were lower for the Asiatic cotton (`49420 per ha) than the BGII hybrid (`62895 per ha). Thus, cultivation of Asiatic absorbent cotton, such as Phule Dhanwantary, could be an alternative option for the rainfed cotton farmers of central India.